BE_VERWALTUNGSGERICHT 100 2017 107 vom 4. Juli 2017 - BE Verwaltungsgericht (2017)
Schulungsort (Entscheid der Erziehungsdirektion des Kantons Bern vom 16. März 2017 - 4800.600.200.07/15 [715364]) | Andere